Effects of nano-SiO2 and polylactide/poly(butylenes adipate-co-terephthalate) packaging bags on quality of Chinese cabbage (Brassica chinensis L.) during shelf life - ZHANG Peiyu; WANG Fanfan; LIN Qiong; DUAN Yuquan (浙江大学学报. 农业与生命科学版, 2020)
The fresh Chinese cabbage was packaged in three different material bags, including polyethylene (PE) bags, polylactide/poly(butylenes adipate-co-terephthalate) (PLA/PBAT) bags, and nano-SiO2 bags, and then stored at 20 ℃ for 8 d. The Chinese cabbage packaged in PE bags was taken as a control, and the effects of different bags on the quality of Chinese cabbage during shelf life were compared. The results showed that nano-SiO2 bags had the best fresh-keeping effects on Chinese cabbage during shelf life, and followed by PLA/PBAT bags. Compared with the control, after packaged in two novel material bags, the respiration rate and ethylene release rate were significantly reduced, and the accumulation of malondialdehyde (MDA) and nitrite was inhibited. Besides, the degradation of chlorophyll and ascorbic acid was also delayed and the higher activities of catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD) were maintained. In general, both PLA/PBAT and nano-SiO2 bags can maintain the quality of Chinese cabbage during shelf life to a certain degree, but the shelf life of Chinese cabbage packaged in PLA/PBAT bags is 2 d, while nano-SiO2 bags can extend the shelf life to 4 d.